Epigenetic control of variation and stochasticity in metabolic disease - Ilaria Panzeri; John Andrew Pospisilik (Elsevier, 2018)
Background: The alarming rise of obesity and its associated comorbidities represents a medical burden and a major global health and economic issue. Understanding etiological mechanisms underpinning susceptibility and therapeutic response is of primary importance. Obesity, diabetes, and metabolic diseases are complex trait disorders with only partial genetic heritability, indicating important roles for environmental programing and epigenetic effects. Scope of the review: We will highlight some of the reasons for the scarce predictability of metabolic diseases. We will outline how genetic variants generate phenotypic variation in disease susceptibility across populations. We will then focus on recent conclusions about epigenetic mechanisms playing a fundamental role in increasing variability and subsequently disease triggering. Major conclusions: Currently, we are unable to predict or mechanistically define how "missing heritability" drives disease. Unravelling this black box of regulatory processes will allow us to move towards a truly personalized and precision medicine. Keywords: Phenotypic variation, Inheritance, Metabolic diseases, Epigenetics